2009
DOI: 10.1108/13555850910950040
|View full text |Cite
|
Sign up to set email alerts
|

When hot and noisy is good

Abstract: Purpose -The purpose of this paper is to extend research on metaphors of consumption to a Chinese cultural setting, specifically examining consumer thoughts related the Chinese concept of renao (hot and noisy). Design/methodology/approach -The Zaltman Metaphor Elicitation Technique (ZMET) was useda photo elicitation approach and semi-structured interviews that surfaced metaphors. Field observation and participative techniques were combined with the 14 interviews, in Taiwan, through a grounded theory approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, the respondents also agreed on the function of food being a communication and socializing tool, which resonates with the findings of prior research (Neely et al, 2014;Niva, 2008). Past study (Warden & Chen, 2009) suggested that Chinese generally associate bustling and crowd to positive food and eating experience. In this paper, we have extended Warden and Chen's (2009) model by revealing the underlying values of sharing or group dining, which is to foster warm relationships with others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the respondents also agreed on the function of food being a communication and socializing tool, which resonates with the findings of prior research (Neely et al, 2014;Niva, 2008). Past study (Warden & Chen, 2009) suggested that Chinese generally associate bustling and crowd to positive food and eating experience. In this paper, we have extended Warden and Chen's (2009) model by revealing the underlying values of sharing or group dining, which is to foster warm relationships with others.…”
Section: Discussionmentioning
confidence: 99%
“…Past study (Warden & Chen, 2009) suggested that Chinese generally associate bustling and crowd to positive food and eating experience. In this paper, we have extended Warden and Chen's (2009) model by revealing the underlying values of sharing or group dining, which is to foster warm relationships with others. This finding has added to the current literature by suggesting a new functional benefit of food.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations